THE PREVALENCE AND RELATED FACTORS OF METABOLIC SYNDROME IN OUTPATIENTS UNDER HEALTH MANAGEMENT OF AN GIANG PROVINCE AT AN GIANG CENTRAL GENERAL HOSPITAL IN 2020 - Nguyen , Thai Bao; Vo , Huynh Trang; Doan, Thanh Hung (Cantho Journal of Medicine and Pharmacy, 2026)
Backgroud: Metabolic syndrome (MetS) is a collection of several cardiovascular and metabolic risk factors. Factors frequently appearing in MetS include: impaired glucose tolerance, obesity, especially abdominal obesity, dyslipidemia causing atherosclerosis, hypertension. Objectives: 1. To determine the prevalence of MetS in outpatients under health management of An Giang province at An Giang central general hospital ;2. Investigation of risk factors of MetS in outpatients under health management of An Giang province at An Giang central general hospital. Materials and methods: A cross-sectional descriptive study of 259 outpatients under health management of An Giang province at Deparment of Internal Medicine A, An Giang central General Hospital from May to December 2020. Results: Among 259 patients studied, the rate of MetS was 70,3% (male accounted for 72.2%, female accounted for 60.5%). The prevalence of MetS increased gradually with age, the highest in the age group 60 - 69 years old (81.1%). There was a significant difference in the incidence of MetS in patients ≥ 60 years old (OR=3.093); overweight, obesity (OR=2.996); have blood dyscrasias (OR=6.163); with hypertension (OR=10.258). There was no association between the risk of MetS and sex. Conclusion: The prevalence of MetS in outpatients under health management of An Giang province at Deparment of Internal Medicine A, An Giang central General Hospital was 70.3%. Factors that increase the risk of MetS are age ≥ 60 years; overweight or obesity; dyslipidemia and hypertension.